P-18 Development of a lower-back muscle activity sensor system for educational support for care workers - MAENAKA, Kazusuke; YOTO, Tsuyoshi Yi; NAKAI, Akira; MURAMATSU, Shigeo; KOMATSU, Takeshi; SHIMOMURA, Yoshihiro (Ningen kogaku. The Japanese journal of ergonomics, 2017)
In training institutions for care workers, incorrect operation often causes a pain in the lower-back to trainees. The instructors have difficulty in judging whether the trainees perform an operation correctly without monitoring muscle activity in the lower-back. Accordingly, the purposes of the present study were (a) to produce a sensor to measure muscle activity in the lower-back and (b) to develop the education support system which shows the instructors a simultaneous display of muscle and physical activities in the lower-back and video of the operations. The experimental sensors consist of six channel electromyogram (EMG) sensors, three-axis acceleration, angular velocity and geomagnetic sensors. The software for data acquisition which records data from individual sensors synchronously was developed using LabVIEW 2015. Using this all-in-one experimental sensor system, five subjects had their lower-back muscle activity measured while lifting a dumbbell. The data acquired was compared to the data from the same experiment monitored by existing, commercially available non-integrated systems. Consequently, the experimental system could record the data smoothly from the sensors on the lower-back as expected. The integrated EMG values of the erector spinae muscles obtained by the experimental system and the commercially available EMG system had a strong positive correlation. Hereafter, our work will be to validate the experimental system by comparing the other data sources to existing sensor systems.